The Cleft Multidisciplinary Collaborative: Establishing a Network to Support Cleft Lip and Palate Research in the United Kingdom. (April 2019) - Sainsbury, David C. G.; Davies, Amy; Wren, Yvonne; Southby, Lucy; Chadha, Ambika; Slator, Rona; Stock, Nicola Marie
Background: As a growing paradigm of health research, trainee collaboratives can influence clinical practice through the generation of cost-effective multicenter audit and research projects. The aims of the present article are to outline and discuss the establishment of a multidisciplinary collaborative in the context of cleft lip and/or palate (CL/P). Methods: The Cleft Multidisciplinary Collaborative (CMC) was formed in April 2016 under the overarching supervision of the National Institute for Health Research. Membership of the CMC is open to all members of the CL/P multidisciplinary team, who are encouraged to submit ideas for new research projects that will benefit clinical practice. Results: To date, 48 clinical participants are involved in the CMC. These participants represent all 17 cleft teams from the United Kingdom and encompass a wide range of disciplines. The CMC has undertaken 2 major projects so far. The first involved collection of phenotype data to support a national cohort study. The second, still in progress, is a systematic review investigating factors associated with outcomes for velopharyngeal competence following cleft palate repair. Conclusions: The concept of a multidisciplinary collaborative in CL/P has been demonstrated through the generation of a United Kingdom-wide network of committed clinicians and researchers and the effective undertaking of 2 large research projects. As the CMC gathers momentum, it hopes to attract funding to support its activities, to promote more involvement from the allied health and nursing professions, to encourage a more ingrained research culture within the CL/P community, and to promote the wider ambition of a global collaborative.